2015
DOI: 10.7150/jca.10638
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of Chromosome 8 Genes in Lung Cancer

Abstract: Chromosomal alterations are frequent events in lung carcinogenesis and usually display regions of focal amplification containing several overexpressed oncogenes. Although gains and losses of chromosomal loci have been reported copy number changes of the individual genes have not been analyzed in lung cancer. In this study 22 genes were analyzed by MLPA in tumors and matched normal tissue samples from 82 patients with non-small cell lung cancer. Gene amplifications were observed in 84% of the samples. Chromosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 48 publications
4
34
0
Order By: Relevance
“…Moreover, similar frequencies of copy number changes and a highly significant correlation between the CDKN2A and CDKN2B genes in our cohort support the fact that different tumor suppressor genes in this region may cooperate in HNSCC . This observation is also in line with our previous findings revealing collaboration of different amplicons in lung cancer . An interesting fact is the report indicating that 9p deletions involving the CDKN2A locus may sometimes occur against a background of copy number gains .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, similar frequencies of copy number changes and a highly significant correlation between the CDKN2A and CDKN2B genes in our cohort support the fact that different tumor suppressor genes in this region may cooperate in HNSCC . This observation is also in line with our previous findings revealing collaboration of different amplicons in lung cancer . An interesting fact is the report indicating that 9p deletions involving the CDKN2A locus may sometimes occur against a background of copy number gains .…”
Section: Discussionsupporting
confidence: 91%
“…Resolution of conventional comparative genomic hybridization (CGH) is not sufficient for the precise identification of the molecular changes on the gene level . Multiplex ligation‐dependent probe amplification (MLPA) is a molecular technique that allows targeting and analysis of up to 50 different chromosomal sequences as well as intragenic rearrangements in a single reaction . The power of MLPA has not been evaluated for the analysis of gene copy numbers in head and neck cancer.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that ZNF703 is overexpressed in 15% of breast cancers that harbor 8p12 amplifications . In our previous study we detected ZNF703 amplification in 43.2% of the NSCLC tumor tissues . Therefore, in this study we investigated the expression of ZNF703 to identify whether overexpression of ZNF703 occurs as a result of amplification in NSCLC.…”
Section: Discussionmentioning
confidence: 92%
“…As a result of chromosomal breaks and rearrangements, oncogenes and tumour suppressor genes which are found at the 8p11‐12 region contribute to tumour development and oncogenesis . The gene coding for the ZNF703 transcription factor is one of the frequently amplified genes in this region . ZNF703 regulates expression of multiple genes involved in transcription modulation, adhesion, motility, differention, stem cell renewal and invasion …”
Section: Discussionmentioning
confidence: 99%